Conceptual principles of stimulating the attraction of investments in reconstruction projects of Ukraine - Vladyslav TEREMETSKYI; Volodymyr USTYMENKO; Olena KUREPINA; Kseniia TOKARIEVA; Mariana MALCHYK; Oleksii FAST; Viktor DOVHAN (Revista Jurídica Portucalense, 2025)
The article’s purpose is to develop the conceptual basis for the formation of a complex investment mechanism combining legal, economic, and organizational investment stimulation tools for the reconstruction of Ukraine in the post-war period. System-structural, logical, dialectical, and dogmatic methods of scientific knowledge were applied, which enabled a thorough study of the regulatory framework, theoretical concepts, and empirical data in the field of investment activity regulation. Complex conceptual frameworks were defined to stimulate the attraction of investments in reconstruction projects in Ukraine after the war, considering the scale of infrastructure destruction. Specific mechanisms and principles that must be applied to ensure effective investment and recovery of the economy are proposed. The need for a comprehensive approach to stimulating investment in the post-war period through the simultaneous application of legal, economic, and organizational mechanisms on the basis of the formation of a favorable investment climate is indicated. The importance of priority stimulation of investments in the restoration of certain sectors of the economy and affected regions, balanced attraction of foreign capital and support of domestic economic entities, and stimulation of "green" and innovative investments for sustainable development was emphasized. The expediency of decentralization of powers in the field of investment policy, activation of international cooperation, and formation of a positive image of Ukraine as an investment-attractive state is substantiated. The scientific novelty of this study consists in the formulation of the latest conceptual approaches to the stimulation of investments in the conditions of post-war reconstruction, taking into account economic realities and legal challenges.